OPTIMASI KUALITAS DAYA HIBRID TURBIN ANGIN DAN PHOTOVOLTAIC - Zainal Abidin (Universitas Islam Lamongan, 2019)
In order to decrease fuel emissions as a staple of electricity generation, renewable energy is one of the choices in the context of green technology. Wind and solar energy are several choices of renewable energy sources that can be used as environmentally friendly power plants without carbon emissions and are cheap. The application of wind turbine and solar photovoltaic hybrids is mostly carried out in several countries, especially in the fulfillment of isolated land. The HOMER application is one application that can be used to simulate wind turbine and photovoltaic hybrids.